MENGGAGAS FORMASI GURU SEBAGAI RASUL AWAM MILENIAL - Role, Yanuarius Hilarius (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The kingdom of God that Jesus proclaimed during his lifetime became the core of the church's message. Since its inception, the church has had the task of proclaiming the Kingdom of God. Efforts to develop the Kingdom of God carried out by the church involve all levels, groups and classes in the church structure. The church as an organization has its own structure. Within it there are so-called hierarchies, monks/nuns and laity. The church is a community of believers, who believe in Christ who is God. This community of believers was formed by Christ himself through the preaching, work and promise of salvation that he proclaimed to every human being. This community contains both divine and human meanings. The divine meaning of this community is a work of the Holy Spirit who provides impetus, a spirit that lives as an organism that continues to develop because of the power of God's own Spirit. Meanwhile, the human meaning lies in human involvement in their free will to develop this community. The role of humans makes this community have a human character. The human character of the Church is shown by the presence of the church as an organization that has a neat and clear structure. The laity in the Catholic Church community constitute the largest number apart from clergy and monks/nuns. With a large number, the laity becomes a very strategic force in order to develop the Catholic church community. This power was really felt in the development of the church from the beginning. The church community as a community of bearers of the good news about the Kingdom of God that was proclaimed by Jesus during his lifetime mostly consists of lay people. However, the formation process as an integral opportunity for the formation of strong lay people has not been taken seriously compared to the formation process for clergy and monks/nuns.